1999
DOI: 10.1038/sj.bjp.0702328
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte‐endothelial cell adhesion: avenues for therapeutic intervention

Abstract: British Journal of Pharmacology (1999) 126, 537–550; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0
10

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(180 citation statements)
references
References 96 publications
7
160
0
10
Order By: Relevance
“…These findings are in accordance with a previous study in which the percentages of basophils and eosinophils, leukocytes and monocytes were reduced by glucocorticoids in stressed animals (O'Connor et al, 2000). This inhibition is mediated at the level of cytokine gene transcription, and by inhibition of the production of arachidonic acid-derived proinflammatory substances (Panes et al, 2009). However, rise of blood neutrophil concentrations in the presence of glucocorticoids because of impaired endothelial cell adhesion, and consequently impaired diapedesis and migration to inflammatory sites (Doukas et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with a previous study in which the percentages of basophils and eosinophils, leukocytes and monocytes were reduced by glucocorticoids in stressed animals (O'Connor et al, 2000). This inhibition is mediated at the level of cytokine gene transcription, and by inhibition of the production of arachidonic acid-derived proinflammatory substances (Panes et al, 2009). However, rise of blood neutrophil concentrations in the presence of glucocorticoids because of impaired endothelial cell adhesion, and consequently impaired diapedesis and migration to inflammatory sites (Doukas et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…In 1989, Osborn et al (24) reported that IL-1 was able to augment the adhesiveness of the vascular endothelium. This cytokine, along with others such as TNF-␣, up-regulate ICAM-1 and E-selectin expression (25). Our results, from experiments conducted in normal skin, indicate that IL-1␤ induced significant neutrophil accumulation at 0.3 pmol/site, but this was not observed with higher doses, with similar results in wild-type and knockout mice.…”
Section: Discussionsupporting
confidence: 69%
“…IL-1␤ together with TNF-␣ are potent inducers of ICAM-1 expression which has previously been shown to be a requirement for neutrophil recruitment after airway instillation of LPS (24,25,35). Therefore, we postulated that the beneficial effect of ebselen might occur through the ability of this agent to prevent lung ICAM-1 expression.…”
Section: Effect Of Ebselen On Lung Icam-1 Expressionmentioning
confidence: 98%